2008
DOI: 10.1111/j.1399-0012.2008.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of ureteral carcinoma in a transplanted kidney presenting by early stenosis of the proximal ureter

Abstract: A 71-yr-old male kidney transplant recipient suffered from delayed graft function. Eighty days after transplantation complete obstruction of the proximal ureter was observed, complicated by recurrent urinary tract infections. Two months later, the donor kidney was removed because of infectious complications and inadequate arterial perfusion. Histological examination of the removed graft showed signs of rejection as well as a low-grade papillary urothelial cell carcinoma of donor origin in the ureter. The remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, TCCtu appears to be rare, with an incidence reported between 0.15 and 0.78% . Our systematic literature review identified five cases in Penn's cancer registry and 24 additional cases . We report the largest case‐series of four patients (Table ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, TCCtu appears to be rare, with an incidence reported between 0.15 and 0.78% . Our systematic literature review identified five cases in Penn's cancer registry and 24 additional cases . We report the largest case‐series of four patients (Table ).…”
Section: Discussionmentioning
confidence: 90%
“…The overall risk of DTC is low, estimated at 0.06% (23). Only one case of DTC TCCtu has been described, and donor genetic origin was established (8). We recently declined a potential RT when a TCC was discovered in the dilated distal ureter of the donor organ (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous reported cases had documented death in 7/36. 10,28,30,31 No follow-up information was also available for further 7/36 3,34,35 and for the remnant cases, there is often a limited follow-up. Subsequent successful transplantation has been reported in selected cases after an extended disease-free interval 33 ; whilst we are unable to comment based on the short duration of follow-up, patients could potentially be considered for further transplantation after an appropriate disease-free period, generally 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Late ureteral obstructions generally after the first month or even at years posttransplant are secondary to chronic ischemia which leads to chronic fibrosis and strictures. Other cause includes compressive limphoceles or pelvic masses, ureteral lithiasis and rarely obstruction by ureteral carcinoma (Huurman, Baranski et al 2008) or fungus ball (Vuruskan, Ersoy et al 2005). The clinical presentation includes pain over the surgical site, decreased urine volume leading to oligoanuria and rise in blood pressure secondary to impaired renal function.…”
Section: Ureteral Obstructionmentioning
confidence: 99%